The Influence Of Knowledge Management And Entrepreneurial Orientation On Business Performance Mediated By Competitive Advantage (A Study On Smes In The City Of Bandar Lampung) - Elmawalida Fakhrunnisa; Astrid Puspaningrum; Desi Tri Kurniawati (Journal Research of Social Science, Economics, and Management, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economic growth of a country. The contribution of MSMEs to Indonesia's GDP experienced a depression due to the emergence of Covid-19 at the beginning of 2020. However, two years after the government declared pandemic for Indonesia, the performance of MSMEs has begun to recover from its downturn. This is shown by the increase in the contribution of MSMEs to Indonesia's GDP and employment in Indonesia. Moreover, the performance of MSMEs in Bandar Lampung City has also experienced an improvement as shown by an increase in MSME profits. This research aims to analyze the influence of knowledge management and entrepreneurial orientation on business performance in Small and Medium Enterprises (SMEs) as well as the mediating effect of competitive advantage in this relationship. This research uses a quantitative approach to draw conclusions from the proposed hypothesis. Sample was selected using the census method so that the total sample was 44 respondents who were SMEs registered in Dinas Koperasi dan UKM Kota Bandar Lampung. Data collection method uses a questionnaire and the data is analyzed using SEM-PLS with the bootstrap method. The results show that knowledge management, entrepreneurial orientation, and competitive advantage have a direct and significant influence on business performance. Furthermore, competitive advantage was also found to play a mediating role in the relationship between knowledge management and entrepreneurial orientation on business performance.